Gut Microbiome Changes in Captive Plateau Zokors (Eospalax baileyi). (February 2021) - Liu, Daoxin; Song, Pengfei; Yan, Jingyan; Wang, Haijing; Cai, Zhenyuan; Xie, Jiuxiang; Zhang, Tongzuo
Wild-caught animals must cope with drastic lifestyle and dietary changes after being induced to captivity. How the gut microbiome structure of these animals will change in response receives increasing attention. The plateau zokor ( Eospalax baileyi ), a typic subterranean rodent endemic to the Qinghai-Tibet plateau, spends almost the whole life underground and is well adapted to the environmental pressures of both plateau and underground. However, how the gut microbiome of the plateau zokor will change in response to captivity has not been reported to date. This study compared the microbial community structure and functions of 22 plateau zokors before (the WS group) and after being kept in captivity for 15 days (the LS group, fed on carrots) using the 16S rRNA gene via high-throughput sequencing technology. The results showed that the LS group retained 973 of the 977 operational taxonomic units (OTUs) in the WS group, and no new OTUs were found in the LS group. The dominant bacterial phyla were Bacteroides and Firmicutes in both groups. In alpha diversity analysis, the Shannon, Sobs, and ACE indexes of the LS group were significantly lower than those of the WS group. A remarkable difference ( P  < 0.01) between groups was also detected in beta diversity analysis. The UPGMA clustering, NMDS, PCoA, and Anosim results all showed that the intergroup difference was significantly greater than the intragroup difference. And compared with the WS group, the intragroup difference of the gut microbiota in the LS group was much larger, which failed to support the assumption that similar diets should drive convergence of gut microbial communities. PICRUSt revealed that although some functional categories displayed significant differences between groups, the relative abundances of these categories were very close in both groups. Based on all the results, we conclude that as plateau zokors enter captivity for a short time, although the relative abundances of different gut microbiota categories shifted significantly, they can maintain almost all the OTUs and the functions of the gut microbiota in the wild. So, the use of wild-caught plateau zokors in gut microbial studies is acceptable if the time in captivity is short.